Immunogenicity of BNT162b2 mRNA-Based Vaccine against SARS-CoV-2 in People with Cystic Fibrosis According to Disease Characteristics and Maintenance Therapies - Gianfranco Alicandro; Valeria Daccò; Lisa Cariani; Chiara Rosazza; Calogero Sathya Sciarrabba; Federica Ferraro; Chiara Lanfranchi; Paola Medino; Daniela Girelli; Carla Colombo (Biomedicines, 2022)
During the SARS-CoV-2 vaccination campaign, people with CF (pwCF) were considered a clinically vulnerable population. However, data on the immunogenicity of anti-SARS-CoV-2 vaccines in pwCF are lacking. We conducted a prospective study enrolling all patients aged > 12 and who were followed-up in our CF center and received two doses of the BNT162b2 vaccine in the period of March–October 2021. Blood samples were taken from them for the quantification of antibodies to the SARS-CoV-2 spike protein receptor binding domain immediately before receiving the first dose and 3 and 6 months after the second dose. We enrolled 143 patients (median age: 21 years, range: 13–38), 16 of whom had had a previous infection. Geometric mean antibody titer (GMT) 3 months after vaccination was 1355 U/mL (95% CI: 1165–1575) and decreased to 954 U/mL (95% CI: 819–1111) after 6 months (p < 0.0001). GMT was higher among previously infected patients as compared to those naïve to SARS-CoV-2 (6707 vs. 1119 U/mL at 3 months and 4299 vs. 796 U/mL at 6 months, p < 0.0001) with no significant differences in the rate of decline over time (p = 0.135). All pwCF mounted an antibody response after two doses of the BNT162b2 vaccine, which waned at 6 months from vaccination. Age ≥ 30 years and the use of inhaled corticosteroids were associated with a lower humoral response. Between the second and the third doses, nine episodes of vaccine breakthrough infections were observed.